Magnitude of cesarean-section and associated factors among diabetic mothers in Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia: A cross-sectional study - Eshetu, Bajrond; Balis, Bikila; Daba, Woreknesh; Mekonnen, Bazie; Getachew, Tamirat; Roga, Ephrem Yohanes; Habte, Sisay; Bekele, Habtamu; Ketema, Indeshaw; Debella, Adera (Frontiers in Public Health, 2022)
Background Gestational diabetes is associated with multiple adverse pregnancy outcome as a result of unfavorable labor and delivery process with a consequent increase in obstetric interventions including cesarean-section. Even though diabetes mellitus increases the cesarean-section rate; there is no study conducted in Ethiopia. therefore, this study aimed to assess the magnitude of cesarean-section and associated factors among diabetic mothers in Tikur Ambessa Specialize Hospital, Addis Ababa, Ethiopia. Methods A facility-based retrospective cross-sectional study was conducted in Tikur Anbessa Specialized Hospital from 1 February to 30 April 2018 among 346 diabetic mothers. All required data were extracted from patients' charts using checklists, and incomplete records were excluded. The collected data were entered into Epi data version 4.2 and exported to SPSS version 20 for analysis. Multiple logistic regression models were fitted to identify factors associated with cesarean section. Adjusted odds ratios along with 95% CI were estimated to measure the strength of the association and declared statistical significance at a p-value <0.05. Results The magnitude of cesarean-section was 57.8% (95% CI: 51.7, 63.3). Pregnancy-induced hypertension [AOR: 3.35, (95% CI: (1.22, 9.20)], previous C/S [AOR: 1.62, (95% CI: (2.54, 4.83)], and fetal distress [AOR: 4.36, (95% CI: 1.30, 14.62)] were factors significantly associated with cesarean-section. Conclusion A considerable number of diabetic mothers gave birth by cesarean-section. Pregnancy-induced hypertension, previous cesarean-section, and fetal distress were factors more likely to increase the rate of cesarean-section. Most of the factors were modifiable by following the WHO recommendation for cesarean-section.